Hermeneutics of Transcultural Space: Reading Bersih Desa as a Cultural Text in Musi Rawas - Jamhari Jamhari; Ris’an Rusli; Syahril Jamil; Miftachul Huda; Pathur Rahman (Jaqfi: Jurnal Aqidah dan Filsafat Islam, 2026)
This article critically analyzes the philosophical significance of the Bersih Desa tradition in Musi Rawas Regency through the lens of transcultural hermeneutics. Drawing on the interpretive perspective of Clifford Geertz and the hermeneutics of Hans-Georg Gadamer, this qualitative research examines the ritual as a living “cultural text.” Through fieldwork involving traditional, religious, and community leaders, the study explores how symbol systems operate in a multicultural society. The results show that Bersih Desa goes beyond physical rituals to become a symbol system that integrates cosmological values, social ethics, and collective solidarity between transmigrants and residents. This phenomenon reflects a process of “fusion of horizons,” in which Javanese traditions undergo contextual adaptation and hybridization of values within the transcultural space of Musi Rawas. Ritual symbols are reinterpreted as a medium for value negotiation, giving rise to hybrid identities. Philosophically, Bersih Desa plays a fundamental role in shaping meaning, identity, and social harmony among transmigrant communities